(untitled) (Khairulummah, 2023)
This study observes the historical and ideological influences that contributed to the emergence of communism in Afghanistan. The roots of communism in Afghanistan can be traced back to the early 20th century, when academic and political movements began to challenge traditional monarchical and Islamic institutions. The influence of Marxist-Leninist ideology, spread through educational organizations and literary circles, resonated with Afghan intellectuals seeking modernization and social change. The study concentrations on the People’s Democratic Party of Afghanistan (PDPA), founded in 1965, which played a crucial role in Afghanistan’s communist movement. The PDPA’s ideological divisions, internal power struggles, and eventual rise to power in 1978 are examined. This research provides insights into the complex historical context that shaped Afghanistan’s communist movement, highlighting the interplay between internal and external factors. Understanding these roots is vital for avaricious the complications of Afghanistan’s modern history, including the Soviet occupation, civil war, and ongoing political instability.